1991
DOI: 10.1111/j.1476-5381.1991.tb12549.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the efficacy and affinity of the β2‐adrenoceptor agonist salmeterol in guinea‐pig trachea

Abstract: 1 We have attempted to estimate the affinity and efficacy of the new fl2-adrenoceptor agonist salmeterol in the guinea-pig isolated trachea and to compare these estimates with those obtained for salbutamol. 2 The kinetics of the relaxation to salmeterol were considerably slower than those to salbutamol and the responses were poorly defined. Nevertheless, in experiments employing a cumulative curve design both salmeterol and salbutamol exhibited partial agonist behaviour. Operational model-fitting of these data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 6 publications
(11 reference statements)
7
29
0
Order By: Relevance
“…In fact, DOUGALL et al [17], using adrenaline and isoprenaline as agonists, noted significantly less steep concentration-effect curves in the presence of salmeterol as compared to control curves. More, recently, NALINE et al [18] showed that when isolated human bronchi were incubated in the presence of formoterol, a significant (1 log unit) displacement of the concentration-response curves to adrenaline was observed with long acting β 2 -agonist at a concentration giving a maximal effect.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, DOUGALL et al [17], using adrenaline and isoprenaline as agonists, noted significantly less steep concentration-effect curves in the presence of salmeterol as compared to control curves. More, recently, NALINE et al [18] showed that when isolated human bronchi were incubated in the presence of formoterol, a significant (1 log unit) displacement of the concentration-response curves to adrenaline was observed with long acting β 2 -agonist at a concentration giving a maximal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings concerning the effects of salmeterol on 86Rb+ efflux, parallel the electrophysiological observations (Cook et al, 1993) in guinea-pig trachealis that salmeterol itself fails to cause cellular hyperpolarization but can inhibit the hyperpolarization induced by isoprenaline. We suggest that the weakness of the effects of salmeterol on 86Rb+ efflux from trachealis muscle and on membrane potential, combined with its ability to antagonize a full agonist, may be explicable in terms of its reported (Dougall et al, 1991) low intrinsic efficacy at P2-adrenoceptors.…”
Section: Studies Of86rb+ Efflux From Bovine Trachealismentioning
confidence: 99%
“…These observations provide very strong evidence to suggest that, in contrast to isoprenaline, procaterol and salbutamol, salmeterol is ineffective in provoking the opening of plasmalemmal K+-channels in trachealis muscle. Studies of guinea-pig trachealis pre-contracted with carbachol (Ball et al, 1991;Dougall et al, 1991;Waldeck & Kallstrom, 1991;Cook et al, 1993) have indicated that salmeterol is a partial rather than a full agonist at P2-adrenoceptors. The partial agonist activity of salmeterol was not revealed by comparing the maximal relaxant effects of isoprenaline and salmeterol in histamineprecontracted bovine trachealis (Figure 1 and 2).…”
Section: Studies Of86rb+ Efflux From Bovine Trachealismentioning
confidence: 99%
See 2 more Smart Citations